174. Large scale adoption of statistical process control for patient-specific VMAT quality assurance. (December 2018) - Cilla, S.; Ianiro, A.; Viola, P.; Craus, M.; Deodato, F.; Macchia, G.; Buwenge, M.; Valentini, V.; Morganti, A.G.
Abstract: Purpose: Statistical Process Control (SPC) is a tool widely used in industrial engineering for monitoring, controlling and improving a process through statistical analysis. We applied this strategy for patient-specific VMAT pre-treatment verification. Methods: From 2009, more than 1700 patients were treated with Elekta VMAT at our institution. Plans were re-grouped according to treatment technique and disease sites Group 1: 736 complex treatments using SIB for head-neck, pelvic, brain and other sites; (2) 441 low-risk prostate treatments and (3) 558 extracranial metastasis treated with SBRT. 4942 planar dose measurements were performed with the PTW Seven29 array/Octavius phantom. Three metrics were simultaneously evaluated: (a) γ %: points-percentage with γ -value less than one, (b) γ mean and (c) γ 1%: the near-maximum gamma. Clinical specifications were: γ % > 90%, γ mean < 0.67 and γ 1 % < 2 . Shewhart charts were used to calculate the central (CL), upper control (UCL) and lower control limits (LCL). The capability of the processes was evaluated by means of Cpk indexes. Results: Using 3%/3 mm γ -analysis, results significantly depend on plan complexity. For γ %, CL and LCL were 93.8%, 99.1%, 99.5% and 87.9%, 96.6%, 97.9%, for group 1, 2 and 3 respectively. For γ mean, CL and UCL were 0.42, 0.36, 0.29 and 0.54, 0.49, 0.40, for groups 1, 2 and 3 respectively. For the groups 2 and 3, all processes are in control and within clinical specifications. The Cpl/Cpu indices for γ %, γ mean and γ 1% resulted equal to 2.85, 1.64 and 2.11 in group 2 and 4.20, 2.60 and 2.01 in group 3. For group 1 only the γ mean process is in control; the γ % process is out of control and out of clinical specifications (returning in control with 5%/3 mm specification, with Cpl and Cpu equal to 1.87 and 1.57, respectively). Conclusions: SPC is a powerful tool to quantifiably evaluate the QA process performance in advanced radiotherapy.